Role of APOBEC3 proteins in proteasome inhibitor-mediated reactivation of latent HIV-1 viruses. (19th February 2019) - Timilsina, Uddhav; Ghimire, Dibya; Sharma, Shilpa; Gaur, Ritu
Abstract : Proteasome inhibitors (PIs) have been identified as an emerging class of HIV-1 latency-reversing agents (LRAs). These inhibitors can reactivate latent HIV-1 to produce non-infectious viruses. The mechanism underlying reduced infectivity of reactivated viruses is unknown. In this study, we analysed PI-reactivated viruses using biochemical and virological assays and demonstrated that these PIs stabilized the cellular expression of HIV-1 restriction factor, APOBEC3G, facilitating its packaging in the released viruses. Using infectivity assay and immunoblotting, we observed that the reduction in viral infectivity was due to enhanced levels of functionally active APOBEC3 proteins packaged in the virions. Sequencing of the proviral genome in the target cells revealed the presence of APOBEC3 signature hypermutations. Our study strengthens the role of PIs as bifunctional LRAs and demonstrates that the loss of infectivity of reactivated HIV-1 virions may be due to the increased packaging of APOBEC3 proteins in the virus.